The bonpa indigenous cure system of sowa rigpa or ‘science of healing’ practices: An exploratory study - Singh, Mansi; Sinha, A. K.; Lamba, Rajni (Linguistics and Culture Review, 2021)
The Tibetan medicinal system is among the oldest known healing traditions practiced in the world. History is witness to the fact that there is a vast treasure trove of indigenous knowledge and practices. It offers a holistic treatment system that is aimed at regulating and maintaining an astute balance of the functional principles defining human existence through mind and body. Indigenous medicine is an integral part of the Tibetan culture and has grown and developed across several centuries and geographical spaces. The origins of Tibetan system that pertain to the Bon religious tenets are apparently very old as aspects of the Tibetan medicine have been traced to ancient cultures over 2,500 years old. Traditionally the Tibetan curative system has been known as Sowa-Rigpa Medicine meaning the ‘Science of Healing’. “It is a centuries old system of treatment that is based on a complex approach to diagnosis, incorporating techniques like taking the pulse and conducting an analysis of bodily fluids besides making an examination of the behavior and dietary intake. The medicines are composed of natural materials (e.g., herbs, minerals, plants, leaves etc) and physical therapies (e.g. Tibetan acupuncture, moxabustion, etc) to treat illness.